Eve with long hair - Cetin, Antun (1978)
Stilizirani prikaz žene duge kose
Signatura d.d. olovkom: A. Cetin // 78 ; l.d. olovkom : A/P // "Eve with long hair"
Izvornik digitaliziran
Keywords: Bakropisi; Akvatinte